DEKONSTRUKSI IDENTITAS DAN REALITAS DALAM NOVEL CALABAI: ANALISIS POSTMODERNISME - Asia M, Asia M; Ridwan, Ridwan; Ratih, Ratih (Universitas Andalas, 2024)
This research aims to describe the construction of identity and reality in the novel Calabai by Pepi Al-Bayqunie. The main data source for this research is the novel Calabai by Pepi Al-Bayqunie the method use is qualitative analysis using literature study as a data collection technique. The theory used is Jacques Derrida’s theory of deconstruction. The results of the research show that there is a construction of identity and reality in the character Saidi in the novel Calabai by Pepi Al-Bayqunie the identity presented by the main character in the novel Calabai by Pepi Al-Bayqunie is the existence of a women’s soul that resides in a Saidi who is actually a man and the reality that exists in every event that comes to Saidi as a women with a soul and a bissu. Saidi, who was initially the object of insults, calabai, which was considered a disaster, was actually the opposite of the reality experienced by Saidi in Segeri. It never crossed his mind that a man with a woman’s soul would become the person modt respected and respected by others.